EPITAPHS OF THE POST-MONGOL ERA. EXPERIENCE OF COMPARATIVE RESEARCH - Babadzanov, Bahtiar Miraimovic; Kurumbaev, Ajbulat Samuratovic (History, Archeology and Ethnography of the Caucasus, 2023)
The collapse of the Golden Horde at the end of the 14th century coincided with the expansion of the tradition of establishing tombstones with Arabic epigraphy. This did not at all mean mutual cultural isolation of those ethnic groups that were part of the ulus of Jochi Khan, spread over a large territory of Eurasia. The most revealing indicator of religious and, in general, cultural mutual influences of large and small ethno-political groups can be their tombstones in the form of steles and, less often, in the form of prismatic stones (“chests”). This article offers reviews of some groups of monuments of Western Kazakhstan in the context of obvious analogues with tombstones of the North Caucasus (especially in the Nogai steppe). The similarities are sometimes very obvious (forms of epitaphs, tamgas, types of tombstones, etc.). This allows us to talk about similar funeral and ritual traditions, clan structures, and forms of cult of the dead among the peoples neighboring in the steppes and cities of the Eurasian space. The study of tombstones of the Eurasian steppes as remnants of material culture, as objects of art, is in its infancy. The result of formalized descriptions and incomplete interpretations of the epigraphy of tombstones is sad. This written source turned out to be “auxiliary material”, often serving for dating or classification of clan associations and their tamgas. Social analysis or cultural contexts remain aside. These circumstances force us to look for new interpretive models, bearing in mind that the tombstones and their texts were created in certain historical conditions and in a social environment for which they were part of their ritual practices.